Электронный курс для дистанционного обучения по микроконтроллерам с элементами тестирования - Лысенков, H. A.; Рогачев, Б. А.; Свитенко, В. Н. (УАДО, 2002)
It is offered at creation of electronic courses to utilize technology of databases. Within the framework of remote teaching the computer inspection of knowledge on studied themes and implementation of the jobs on a laboratory practical works is envisaged. The results of studies utilized at working a teaching program on microcontrollers
Keywords: дистанционное обучение; электронный курс